Analisis Perbedaan Peningkatan Pengetahuan pada Penyuluhan Kesehatan Menggunakan Survivor dengan Non Survivor tentang SADARI pada Wanita Usia Subur di Kota Palangka Raya - Rena Oki Alestari; Meyska Widyandini; Lelly Oktarina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Cancer is one of the leading causes of death around the world. The government’s efforts in the early detection of breast cancer have not been achieved. The purpose of the study is to analyze the improvement difference in knowledge of health education by survivors with the non-survivors of SADARI on women in their fertile period. This study used quasi-experimental research, with a pretest-posttest control group design. There were 78 respondents of 20-30 years old women in their fertile period that were randomly selected in the Prenggan district. This study used a questionnaire of knowledge and attitude of SADARI, skill assessment form of SADARI, modules, and leaflets. The data was analyzed using the Independent sample T-test. There was a significant difference in knowledge improvement between survivor and non-survivor (activist) counseling with ρ = 0.005 <0.05. Survivors as a resource are better in improving knowledge about SADARI on women in their fertile period.